Hubungan Pengetahuan Dan Self Care (perawatan diri) Dengan Kualitas Hidup Pasien Gagal Jantung Di Wilayah Kerja Puskesmas Ranap Inap Kemiling Kota Bandar Lampung - Irma Fitriyan; Djunizar Djamaludin; Eka Yudha Chrisanto (Universitas Malahayati Lampung, 2021)
ABSTRAK : RELATIONSHIP OF KNOWLEDGE AND SELF CARE WITH QUALITY OF LIFE HEART FAILURE PATIENT IN THE WORKING AREA OF KEMILING PUSKESMAS BANDAR LAMPUNGIntroduction : Based on doctor’s diagnosa in Lampung province witch is 1,3% heart disease strikes women more than men with comparison 1,6 : 1,3% and in urban area more spread than rural area.Purpose : to known relationship of knowledge and self care with quality of life heart failure patient in the working area of kemiling puskesmas bandar lampung 2020Methods : quantitative research type, analytic survey research plan with a cross sectional approach population and samples in this research patients with heart failure are 30 respondents. Univariate and bivariate data analysis used the chi square test.Result : distribution of knowledge 15 respondents (50,0%) heart failure with a good knowledge, 16 respondents (53,3%) self care with low category. 16 respondents (53,3%) category good quality of life, the results of statistical tests using the chi square test obtained p-value 0.010 (0.05), p-value 0.003 (0.05)Conclusion : p-value 0.010 (0.05) that means no relationship with knowledge and quality of life for heart failure patients. the results of statistical test using the chi square test obtained p-value 0.003 (0.05). Thats means that there is a relationship between self-care and the quality of life of patients with heart failure. Health workers get input for counseling and treatment for heart failure patient, and get a good quality of life.Keywords : knowledge, self care, quality of life